Impact of HLA alloimmunization on clinical outcomes of severe aplastic anemia treated with immunosuppressive therapy - Jibran Durrani; Leonard N. Chen; Ruba N. Shalhoub; Valentina Baez; Joshua Glass; Nu Ri Cha; Xiaoyang Ma; Zhijie Wu; Shouguo Gao; Jennifer Lotter; Olga Rios; Colin O. Wu; et al. (Blood Advances)
Abstract: Immune aplastic anemia (iAA) frequently results in transfusion dependence on platelets and packed red blood cells, increasing the risk for complications. The most common immune-mediated cause for platelet-transfusion refractoriness is alloimmunization with HLA antibody (Ab) to nonself class I antigens. The clinical impact of the HLA alloimmunization has not been well studied in patients with iAA. We investigated the clinical relevance of HLA alloimmunization in our large cohort of patients with iAA from 5 prospective trials and correlated with disease outcomes. Of 444 patients with severe AA treated with immunosuppressive therapy (IST), 99 (22%) had HLA alloimmunization. The presence of HLA Ab was associated with shorter overall survival, reduced responses to IST and higher risk of clonal evolution. Our data suggest that HLA alloimmunization is a marker of disease outcome. Furthermore, using single-cell RNA sequencing, we show enhanced activation of both complement-mediated pathways and the adaptive immune system in alloimmunized patients, indicating an interconnection between immune compartments.